Controlled potential electrodeposition and characterization of znte thin films on indium tin oxides - Mohamad, Souad A.; Basirun, Wan Jefrey; Ibrahim, Zainol Abidin; Mohd Arof, Abdul Kariem; Ebadi, Mehdi (Trans Tech Publications, Switzerland, 2011)
Electrodeposition of ZnTe thin films by controlled potential method from aqueous solutions on ITO were done to investigate characteristics suitable as a window material in solar cells technology. The influence deposition of potential towards the Zn:Te ratio and the crystallinity are discussed. The electrodeposited films were investigated by using X-Ray Diffraction and Energy Dispersive Analysis of X-Ray. The Te content decreases at higher deposition potentials.